THE IMPACT OF GOVERNMENT SUPPORT ON FIRM PERFORMANCE IN VIETNAM: NEW EVIDENCE FROM A DYNAMIC APPROACH - Hoai Thu Thi Nguyen; Huong Vu Van; Francesca Bartolacci; Tuyen Quang Tran (Asian Academy of Management Journal, 2018)
Using a sample of private manufacturing small- and medium-sized enterprises (SMEs) in the period 2007–2015, this paper examines the effect of government support on firms’ financial performance in Vietnam. Contrary to many previous studies, the study finds that government assistance affects firms’ financial performance after controlling for heterogeneity, unobservable factors, and dynamic endogeneity. The finding supports the viewpoint of institutional theory. The study also reveals that assistance measures, such as tax exemptions, soft loans, and investment incentives to promote financial performance, are vital for the development of Vietnamese private SMEs.